BIOECOLOGICAL CHARACTERISTICS OF SORGHUM VARIETIES - Norboyeva Umida Toshtemirovna; Jurayeva Nilufar Oblakulovna (Modern American Journals, 2025)
The article contains information about the bioecological characteristics of sorghum varieties, in which it is expressed that the varieties adaptability to environmental conditions, the activity of soil and air drying, grain yield, productivity, the ability to accumulate sugar, the value of indicators of the chemical composition of the seed are directly related to the conditions of their cultivation, irrigation regime, soil and climate factors. properties and information about their changes in different degrees depending on the properties of resistance to stress factors.
Keywords: Sorghum varieties, sorghum biology, sorghum, productivity, grain chemical composition, environmental factors, dry matter unit, drought, seed production, blue mass, economic values, phytoimprovement, quality harvest.